Updating a Systematic Literature Review on Knowledge Management Diagnostics in Software Development Organizations - Alves, Daniela dos Santos; Smek, Deivid José; Souza, Érica Ferreira de; Felizardo, Katia Romero; Vijaykumar, Nandamudi L. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
Context: In the rapidly evolving software development landscape, organizations face the constant challenge to work with the generated knowledge. Knowledge Management (KM) can be applied to efficiently manage the knowledge in software development organizations and ensure the product quality. However, although there are several KM approaches, carrying out a KM diagnosis in the organizations can identify which knowledge activities present the best cost-benefit for the organization. There are several KM approaches suggested in the literature. But it is quite relevant to carry out a KM diagnosis in the organizations to clearly identify which knowledge activities can present the best cost-benefit aspect within the organizations. A Systematic Literature Review (SLR) was published in 2018, presenting evidence on KM diagnosis in software development organizations. From an assessment of this SLR and the current state of this research topic, we noticed that the 2018’ SLR needed maintenance with an update. Objective: This study aims to update and extend the results produced in this previous SLR. Method: We conducted the 2018 SLR update, considering a new database, backward and forward snowballing, and more analyses of the extracted data. Results: From the SLR update, 16 new studies on KM diagnoses in Software Engineering context were identified. Conclusion: In Software Engineering, consolidated models continue lacking for applying KM diagnostics. Moreover, computational approaches to provide automated support in the diagnosis application and analysis are not quite well explored.